PELAKSANAAN PRINSIP KETERBUKAAN - Endang Retnowati (Perspektif, 2002)
Stock Exchange, as an alternative financing for business world, plays a very important role in national development activity. Accordingly, a regulation that gives a legal protection for investors become crucial. One of the regulations of that purpose has been established i.e. Regulation no. 8/1945 of Stock Exchange, based on transparency principle, mentioned that every company that will conduct an initial public offering should published a prospectus. Prospectus is a written, detail and thorough information about the company provided for investor that interests to buy the stock.